Bupivacaine Blocks N-Type Inactivating K(v) Channels in the Open State: No Allosteric Effect on Inactivation Kinetics - Nilsson, Johanna (The Biophysical Society, 2008)
Local anesthetics bind to ion channels in a state-dependent manner. For noninactivating voltage-gated K channels the binding mainly occurs in the open state, while for voltage-gated inactivating Na channels it is assumed to occur mainly in inactivated states, leading to an allosterically caused increase in the inactivation probability, reflected in a negative shift of the steady-state inactivation curve, prolonged recovery from inactivation, and a frequency-dependent block. How local anesthetics bind to N-type inactivating K channels is less explored. In this study, we have compared bupivacaine effects on inactivating (Shaker and K(v)3.4) and noninactivating (Shaker-IR and K(v)3.2) channels, expressed in Xenopus oocytes. Bupivacaine was found to block these channels time-dependently without shifting the steady-state inactivation curve markedly, without a prolonged recovery from inactivation, and without a frequency-dependent block. An analysis, including computational testing of kinetic models, suggests binding to the channel mainly in the open state, with affinities close to those estimated for corresponding noninactivating channels (300 and 280 μM for Shaker and Shaker-IR, and 60 and 90 μM for K(v)3.4 and K(v)3.2). The similar magnitudes of K(d), as well as of blocking and unblocking rate constants for inactivating and noninactivating Shaker channels, most likely exclude allosteric interactions between the inactivation mechanism and the binding site. The relevance of these results for understanding the action of local anesthetics on Na channels is discussed.